UJI KONSUMSI BAHAN BAKAR MESIN PENCACAH PLASTIK - Jaelani, M Abdul Kodir (Nozzle : Journal Mechanical Engineering, 2024)
Home industry technology is increasingly advanced so as to provide convenience for the community in processing plastic waste which is very disturbing to the environment so that plastic waste can be processed into plastic seeds which will later become raw materials for making such as flower pots, bricks and so on. the results of enumeration using fuel variations on the driving engine with diesel fuel for 5 minutes with an engine speed of 2000 rpm with the results of fuel consumption 112.5 ml and the results of counting 5.1 kg, while the results of enumeration using dexlite fuel for 5 minutes with an engine speed of 2000 rpm the fuel consumption is 100 ml and the results are 5.1 kg, for fuel pertamina dex for 5 minutes with an engine speed of 2000 rpm the fuel consumption is 87.5 ml and the results are 5 kg.